Development and evaluation of the Singapore Caregiver Quality of Life Scale - Dementia - Yin Bun Cheung; Irene Teo; Wee Shiong Lim; Allyn Hum; Shirlyn H. S. Neo; Grace M. Yang; Geok Ling Lee; Gretchen Tan; Dennis C. C. Seow (SpringerOpen, 2020)
Abstract Purpose To develop and evaluate a measurement scale for multi-domain assessment of the quality of life of family caregivers of persons with dementia (PWD) in Singapore, a multi-ethic society in South-East Asia where English is the lingua franca. Methods Items from the Singapore Caregiver Quality of Life Scale (SCQOLS), which was originally developed in the context of advanced cancers, were adopted as candidate items. Furthermore, a multi-disciplinary panel reviewed dementia-specific caregiver quality of life scales to identified items not covered in SCQOLS for inclusion as candidate items. A pilot study of 31 family caregivers of PWD was conducted to solicit inputs on candidate items; 102 family caregivers of PWD were surveyed for evaluation of the scale's measurement properties. Results Factor analysis confirmed a 5-domain structure of the 63 candidate items. The Root Mean Square Error of Approximation was 0.056 and Comparative Fit Index was 0.928. Convergent validity of the total and domain scores was demonstrated in terms of correlation with the Brief Assessment Scale for Caregivers and its sub-scales. The scores also showed an expected pattern of correlation with hours spent on caregiving per week. Known-group validity was demonstrated by differences in mean scores between functional staging groups. Cronbach's alpha of the total and domain scores ranged from 0.89 to 0.95. Test-retest reliability (intraclass correlation coefficient) ranged from 0.77 to 0.92. Conclusions The Singapore Caregiver Quality of Life Scale - Dementia (SCQOLS-D) is a quality of life measurement scale for family caregivers of persons with dementia that is valid and reliable.